Pengaruh Gaya Kepemimpinan, Disiplin Kerja, dan Kompensasi Kerja terhadap Kinerja Pegawai Negeri Sipil Badan Pembekalan Tentara Nasional Indonesia: Studi Kasus Pegawai Negeri Sipil Babek TNI - Azhira Dwi Oktavianis (Pusat Riset dan Inovasi Nasional, 2024)
Quality human resources (HR) is one of the basic capitals of development. Efforts to improve and develop the quality of human resources have become the main requirement for a nation in the republic of Indonesia to be able to compete at the global level. In the era of globalization and increasingly connected economies, countries compete with each other to create innovation, attract investment, and expand export markets. Qualified human resources are better able to meet these challenges, as they have the knowledge, skills and ability to adapt to change. Quality human resources encourage innovation and creativity, they have the ability to solve problems, and develop new technologies.